THE STAGES OF CREATING A DIGITAL GEOLOGICAL MODEL AND THE MAIN TYPES OF GEOLOGICAL AND HYDRODYNAMIC SIMULATIONS USING - Turdiyev, Shoxjaxon (Innovatsion texnologiyalar, 2024)
This article is a study of the stages of creating a digital geological model using the example of the oil and gas condensate field "Sherkent". The methods of collecting and processing geological data, including geophysical and geological studies, as well as the use of modern technologies for the formation of three-dimensional models of underground structures are considered. The main attention is paid to the analysis of the main types of geological and hydrodynamic modeling, including their application to estimate hydrocarbon reserves and optimize production processes at the “Sherkent” field. Specific examples of using models to predict changes in the geological structure and dynamics of underground fluids are given. The research consists in discussing the practical applicability of digital geological and hydrodynamic models using the example of “Sherkent”, which provides a valuable contribution to the methodology of working with oil and gas fields and modern modeling technologies in the geological industry